Cambridge Checkpoint Mathematics Practice , Book 8 - Greg Byrd; Lynn Byrd, Chris Pearce (Cambridge University Press, 2013)
Written by well-respected authors, the Cambridge Checkpoint Mathematics suite provides a comprehensive structured resource which covers the full Cambridge Secondary 1 Mathematics framework in three stages. This Practice Book for Stage 8 contains further exercise questions for practice in the classroom or at home. It provides coverage of the Problem Solving section framework, with questions relating to the framework statements highlighted.
Grade 7
Keywords: Checkpoint Math -- Checkpoint Math